2018
DOI: 10.1186/s13046-018-0771-x
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: LncRNA TUG1 promoted KIAA1199 expression via miR-600 to accelerate cell metastasis and epithelial-mesenchymal transition in colorectal cancer

Abstract: BackgroundLncRNA TUG1 has been reported to be highly expressed in CRC samples and cells and promoted metastasis by affecting EMT, indicating a poor prognosis for colorectal cancer (CRC). In this study, we determined the underlying mechanism for tumor oncogenesis of lncRNA TUG1 in CRC metastasis.MethodsThe expressions of miR-600 and KIAA1199 in 76 CRC patients and CRC cells and CRC metastatic tissues were determined using qRT-PCR. Epithelial-mesenchymal transition (EMT)-related proteins were determined using we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
57
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 84 publications
(58 citation statements)
references
References 27 publications
1
57
0
Order By: Relevance
“…Increasing evidence supports the important role of EMT in oncogenesis . Induction of the EMT promotes cell invasion, migration, and metastasis, which confers stem‐cell‐like characteristics on cancer cells, and induces therapeutic resistance .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing evidence supports the important role of EMT in oncogenesis . Induction of the EMT promotes cell invasion, migration, and metastasis, which confers stem‐cell‐like characteristics on cancer cells, and induces therapeutic resistance .…”
Section: Discussionmentioning
confidence: 99%
“…However, downregulation miR-600 expression reversed the circPIP5K1A-silencing-induced inhibition of metastasis and Increasing evidence supports the important role of EMT in oncogenesis. 35,36 Induction of the EMT promotes cell invasion, migration, and metastasis, which confers stem-celllike characteristics on cancer cells, and induces therapeutic resistance. 37,38 Cellular signaling responses to hypoxia and inflammation involve crosstalk through upregulation of HIF-1α and associated tumorigenic activities, which are mediated by the inflammatory cytokine interferon-α.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that cytoplasmic lncRNAs generally function as ceRNAs to regulate mRNA expression via sponging versatile miRNAs, thereby playing a pivotal role in cancer metastasis (Lian et al , ; Shan et al , ; Sun et al , ; Wang and Kong, ; Yan et al , ). In fact, lncRNAs exert their functions in several biological processes via interaction with DNA, proteins, and RNAs, which is dependent on the subcellular localization of the lncRNAs within the cells to a large extent (Chen et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…In‐depth studies have demonstrated that lncRNAs acted as a vital regulatory role in malignancies as competing endogenous RNAs. LncRNA TUG1 accelerates cells invasion in colorectal cancer via targeting miR‐600 . LncRNA SNHG16 accelerates the cancer cells migration and invasion abilities through sponging miR‐520d‐3p and targeting STAT3 in hemangioma .…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA TUG1 accelerates cells invasion in colorectal cancer via targeting miR-600. 23 LncRNA SNHG16 accelerates the cancer cells migration and invasion abilities through sponging miR-520d-3p and targeting STAT3 in hemangioma. 24 HOTAIR facilitates the tumor progression in breast cancer cells via downregulation of miR-20a-5p and upregulation of HMGA2.…”
Section: Discussionmentioning
confidence: 99%